Verbal Power Duel: Verbal Combat Strategies in Shakespeare's Julius Caesar: Brutus Versus Antony (KEMANUSIAAN The Asian Journal of Humanities, 2009)
In A Glossary of Contemporary Literary Theory, Jeremy Hawthorn refers to Cultural Materialism as an "umbrella term" that allows itself the opulence to utilise a wide range of tools and theories from many different disciplines. This allows us to justify the nature of both commonly acknowledged and abstruse socio-cultural episteme and discourse, one of the most prominent of which is the issue of power and power relations. This paper, which was originally part of a larger body of work on Cultural Materialism, tries to draw upon a few different theories to examine the confrontational relationship that exists between the two prominent characters of Shakespeare's (1953) Julius Caesar (namely Antony and Brutus), as represented by the duel-like orations of the two characters. The main goal of the paper is to demonstrate how Antony is able to manipulate the words of Brutus against him and thus succeed in captivating the crowd. The theoretical discussions drawn upon in this article will include Austin's (1999) ideas on language as action, Bourdieu's (1999) argument of dialogue as contest and Hutchby's (1999) findings on turn-taking strategies. This paper will also incorporate Paul Grice's Cooperative Principle, introduced in his "Logic and Conversation" (1999). This principle argues that the flouting of any of Grice's four maxims by the characters is meaningful and effective because it introduces an "implicature" in the political and social context in which the pieces of discourse take place.